Знахідки люльок для куріння тютюну XVII—XVIII ст. з розкопок на Поділлі - Чекановський, А.А. (Археологія і давня історія України, 2018)
Стаття присвячена знахідкам люльок для
куріння тютюну з розкопок на території Меджибізької фортеці і у м. Городок (Хмельницька
обл.). Розглянуто аналогії знахідкам з цих колекцій серед люльок з різних районів України, з території
Південно-Східної і Центральної Європи. Дана спроба визначити регіональну специфіку поширення
різних типів керамічних люльок XVII—XVIII ст. на Поділлі. The article focuses on finds of pipes for smoking
tobacco from excavations in Medzhybizh fortress and
in Horodok town (Khmelnitskyi regoin of Ukraine). Analogs to this collection items from various sites of
Ukraine, South East and central Europe are examined. Here is an attempt to identify the local particularity of
the different smoking pipes types spreading in Podillya in the 17th—18th centuries. Styles of pipes which have
counterparts in the Black Sea, in the Central Ukraine and in the Balkans were widespread in the territory
of Podillya in the second half of the seventeenth and nineteenth centuries. The similarity of the pipes type
and variations, the presence of the same varieties is also an indicator of the ways and time of the spread
of technological and decorative traditions. Pipes are an indicator of the links between of some micro-regions
with others. Variations of pipes show the presence of certain ethnic and social groups.